Application of Cationic Conjugated Polymer–Outer Membrane Vesicle Complexes in Inhibiting Red Blood Cell Aggregation - He, Ping; Zhang, Endong; Qi, Ruilian; Lv, Fengting; Liu, Libing; Wang, Shu (Organic Materials, 2019)
Cationic conjugated polymers (CCPs) have been attracting a lot of attention in biomedical applications because of their good photoelectric properties and good cell viability. However, positively charged components may reduce the electrostatic repulsion among red blood cells (RBCs) and induce RBC aggregation, which may lead to thrombus. Herein, in this work, we prepared the complexes of CCPs and outer membrane vesicles (OMVs) to inhibit RBC aggregation induced by CCPs and improve the biocompatibility of CCPs. A poly(fluorene-co-phenylene) derivative (PFP), a poly(p-phenylenevinylene) derivative (PPV), and a poly(thiophene) derivative (PMNT) were chosen as the model CCPs, and OMVs were used as the representative of a cell membrane. The CCP–OMV complexes were formed mainly driven by electrostatic interactions. Besides, the electrostatic CCP–OMV complexes were proved to be able to prevent the RBC aggregation induced by CCPs while maintaining the hydrophobic interactions between CCPs and RBCs.
Keywords: cationic conjugated polymers; outer membrane vesicles; inhibition of RBC aggregation